Issues in the surgical management of skin squamous cell cancers in albinos—experience of two surgical oncology units in Burkina Faso - Nayi Zongo; Adeline R. Djiguemde; Parateyandé Bonaventure Yameogo; Abdoul Halim Bagué; Sidy Ka; Bangaly Traoré; Niamba Pascal; Ahmadou Dem (World Journal of Surgical Oncology, 2023)
Abstract Background and objectives Skin cancers in albinos are frequent in sunny countries. The surgeon plays a crucial role in their treatment. The objective was to describe the challenges of surgical management of skin cancer in albinos. Methods Retrospective, descriptive, and multicenter study on skin cancer surgery in albinos performed over the past 14 years in Ouagadougou. We were interested in surgery indications, techniques, and results. Survival was assessed using the Kaplan–Meier method. Comparisons of proportions were made by Student’s t-test. Results The cancers were multiple synchronous in 41.3%. We identified 46 albinos with 71 skin cancers. Surgery was performed in 93%. Lesions were located on the back, upper limbs, and head and face in 40.9%, 30.3%, and 16.7%, respectively. Precancerous lesions were treated concomitantly in 23.6%. The surgery consisted of a lumpectomy. Direct suturing and mobilization of flaps allowed skin coverage in 17.9% and 34.3%, respectively. Lymph node dissection was associated with the limbs in 73.1% of localizations. The average number of lymph nodes removed was 11, with extremes of 7 and 14. Node invasion was noted in 16 out of 19 cases. The resection margins were invaded in 7.5% and required surgical revision. Recurrences were noted in 8.9% of cases. Overall 2-year survival rate was 55.8%. Conclusions Surgery must meet the triple challenge of treating single or multiple synchronous cancers, precancerous lesions, and allowing good healing. Early diagnosis would reduce the rate of secondary healing and improve survival. The absence of extemporaneous histology and the large size of the tumors associated with the delay in diagnosis meant that surgery, whenever possible, was limited to wide and deep resection, to ensure healthy margins.